Cognitive Load Theory: Limiting the GAP between Academics and Students in Accounting and Auditing - Garvey, Anne M.; Gonzalo-Angulo, José Antonio; Parte, Laura (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2017)
The objective of this paper is to investigate if academics and students share similar cognitive structures in relation to the True and Fair View (TFV) concept, a complex accounting principle, which has no official definition and is open to interpretation and professional judgement. A survey method was used to obtain data for this study. The survey allows us to explore academics and students cognitive structures in order to discover differences and the reasons for the variances if any. Our results show that academics and students do not share similar cognitive structures in three areas of interest: i) compliance with accounting rules and the fulfilment of True and Fair View, ii) the need to provide a written definition of True and Fair View, and iii) the interpretation of True and Fair View. The evidence can be interpreted due to the fact that academics and students tend to use different cognitive schemes in problem solving at least in complex concepts such as TFV. The evidence is supported by the cognitive load theory (CLT). We believe that useful financial information can be improved by understanding these differences and by subsequently implementing criteria in order to reduce the gap between academics and students in the area of information comprehension and presentation with the use of schemes, improvement in educational material and other assistance in the application and interpretation of written standards.